2019
DOI: 10.1111/asj.13292
|View full text |Cite
|
Sign up to set email alerts
|

Shiga toxin 2eB‐transgenic lettuce vaccine is effective in protecting weaned piglets from edema disease caused by Shiga toxin‐producing Escherichia coli infection

Abstract: Porcine edema disease (ED) is a toxemia that is caused by enteric infection with Shiga toxin 2e (Stx2e)‐producing Escherichia coli (STEC) and is associated with high mortality. Since ED occurs most frequently during the weaning period, preweaning vaccination of newborn piglets is required. We developed stx2eB‐transgenic lettuce as an oral vaccine candidate against ED and examined its protective efficacy using a piglet STEC infection model. Two serially developed Stx2eB‐lettuce strains, 2BN containing ingredien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 36 publications
(53 reference statements)
2
21
0
Order By: Relevance
“…The expression cassette of 2×Stx2eB was fine-tuned to increase the accumulation of the Stx2eB protein, and the HSPT and 5′-UTR derived from Nicotiana tabacum alcohol dehydrogenase gene were used in combination with the cauliflower mosaic virus 35S RNA promoter (CaMV 35S pro.). We later confirmed that recombinant Stx2eB is functional as a vaccine (Sato et al 2013), and furthermore, three times of oral administration of approximately 1 g dry weight of freeze dried lettuce powder containing 2.3 mg Stx2eB protein relieves the pathogenic symptoms of edema disease in piglets challenged with a virulent STEC strain (Hamabata et al 2019).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The expression cassette of 2×Stx2eB was fine-tuned to increase the accumulation of the Stx2eB protein, and the HSPT and 5′-UTR derived from Nicotiana tabacum alcohol dehydrogenase gene were used in combination with the cauliflower mosaic virus 35S RNA promoter (CaMV 35S pro.). We later confirmed that recombinant Stx2eB is functional as a vaccine (Sato et al 2013), and furthermore, three times of oral administration of approximately 1 g dry weight of freeze dried lettuce powder containing 2.3 mg Stx2eB protein relieves the pathogenic symptoms of edema disease in piglets challenged with a virulent STEC strain (Hamabata et al 2019).…”
Section: Introductionsupporting
confidence: 57%
“…If we apply the vaccine to 10% of piglets, 900,000 doses are needed. We need 6.9 mg of Stx2eB protein to protect one piglet (Hamabata et al 2019), and the accumulation level of Stx2eB in the lettuce is 6 mg per 1 g dry weight (Figure 4). We can obtain about 10 g dry weight of lettuce powder from one lettuce head with approximately 200 g fresh weight, and therefore more than 100,000 heads of lettuce is needed for 900,000 doses.…”
Section: Discussionmentioning
confidence: 99%
“…This data agrees with results from a study by Brand et al ( 40 ) that found a high level of AMR, in particular to tetracycline (50%), sulfamethoxazole (49%), trimethoprim (34%), and ampicillin (26%) in E. coli isolates from pigs. These results and the increasing awareness on drug-resistant E. coli strains, related to the prophylactic use of antibiotics on healthy piglets or as food additive ( 60 ), highlight the need to develop a vaccine against Stx2e-producing isolates as an useful method alternatively to antimicrobials ( 61 ). In addition, an effective vaccine program is desirable in order to prime immunity able to confirm protection to the effect of toxins ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of porcine edema disease, which is a severe and often fatal disease in pigs that is also mediated by Stx (in this case subtype Stx2e), Hamabata et al have recently developed stx2eB-transgenic lettuce for immunization. Infection of piglets with STEC after oral vaccination by feeding the lettuce showed decreased levels of pathogenesis in lettuce-fed piglets (Hamabata et al, 2019).…”
Section: Toxin-targeted Plant-based Vaccinesmentioning
confidence: 94%